EVALUATION OF STORM SURGE MAP FOR SAFETY IMPROVEMENT IN BANGKOK METROPOLITAN REGION, THAILAND - R. I-soon; D. Chaweewan; P. Iamtrakul (International Association of Lowland Technology, 2011)
Recently, there are a number of disaster occurred in several regions worldwide which might be caused of climate change effects. This damage alarmed many researchers to determine the possibility and risk. Bangkok Metropolitan Region (BMR) is low land area which is potentially flooding risk caused by river flood, flash floods and tropical storm in each year. Evacuation approach is necessary to response in disaster event, especially in low lying areas from the potential life-threatening effects of hazards to safe inland. According to study the local people’s perceptions of storm surge in Amphoe Mueng, Samut Prakarn, the result was shown that most samples evacuate to outside Samut Parakarn area by their own vehicles and evacuate immediately when they have been warned from the government. This paper proposed two main objectives which area; 1) Evaluate Risk level of storm surge and relevant hazard in Bangkok Metropolitan Region (BMR) and 2) Evaluate potential evacuation by overlay between building density in Bangkok Metropolitan Region and road network. Geographic Information System (GIS) was employed to analyze hazard risk level with Spatial Analysis technique.